Development of the gel-mask composition with nettle juice intended for telogen effluvium cutaneous application - M. I. Fedorovska; N. P. Polovko; O. P. Strilets (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Taking into account the frequency of telogen effluvium in women, pharmaceutical market demand, a wide range of pharmacological effects of plant biologically active substances, it is important to develop a new medicinal cosmetic remedy in the form of a gel-mask with nettle juice. The aim of the work - the gel-mask composition development by the results of rheological, biological, microbiological and microscopic studies. The objects of the experiment were gel-mask model specimens with different ratios of nettle juice and auxiliary substances, gel base samples in combination with essential oils and different content of solubilizer PEG-40 hydrogenated castor oil (PEG-40 hсo). The structural viscosity was determined on a brookfield-type viscometer at a temperature of 20 ºc and a spindle speed of 20 rpm. The nettle juice optimal concentration was substantiated on a paramecium caudatum biological model with studying of gel-mask antioxidant properties. effectiveness confirmation of 0.1% potassium sorbate preservative was carried out using the method of the Ukraine state pharmacopoeia 2.0 (USP 2.0), paragraph 5.1.3. The influence of the peg-40 hсo concentration on the essential oil dispersion degree was studied with microscopic method. Considering influence of the auxiliary substances and nettle juice concentration on the gel-mask structural viscosity, the ingredients' correlations were selected which reached the required viscosity limit for gels (2 000-10 000 mpa∙s), namely: carbopol ultrez 10 and sodium alginate by 0.5 %, potassium sorbate - 0.1 %, nettle juice - 10-20 the optimal concentration of nettle juice was 15%. It was justified by the results of the study of the antioxidant properties of the experimental samples on paramecium caudatum infusoria. The conducted microbiological studies confirmed the effectiveness of the application of 0.1% potassium sorbate preservative, which meets the requirements of criterion a for the USP 2.0. The influence of solubilizer peg-40 hco on the degree of mixture of essential oils dispersion when distributed on a gel basis was studied. it was confirmed that the optimal concentration of PEG-40 hco is 0.4%, namely the ratio 1:1 according to the content of the perfume. According to the complex experimental researches, the optimal composition of the gel-mask with nettle juice intended for telogen effluvium cutaneous application has been worked out.